Experimental and numerical investigation of ventilated cavitating flow with special emphasis on gas leakage behavior and re-entrant jet dynamics. (1st November 2015) - Wang, Zhiying; Huang, Biao; Wang, Guoyu; Zhang, Mindi; Wang, Fufeng
Abstract: The objective of this paper is to investigate the ventilated cavitating flow structure by combining experimental and numerical methods. A high-speed camera technique is used to record cavity evolution patterns. The numerical simulation is performed by CFX with a free surface model and a filter-based model, and the gravity effect is considered. The results show when the gas entrainment coefficient Q v is constant, two typical mechanisms of the gas leakage exist at different Fround numbers Fr, namely toroidal vortices mode and two hollow tube vortices mode. With the increasing of Fr, the cavity would transfer from the two hollow tube vortices to the toroidal vortices. Moreover, when the Fr number keeps constant, the enlargement of the cavity causes the gravitational effect to be more significant for the case of larger value of Q v . The detail analysis of re-entrant behaviors is also conducted. One type of re-entrant flow is unsteady with air cluster being periodically rejected at the rear of the cavity. The other type of the re-entrant flow shows that the majority of the cavity is transparent, only the region at the tail of the cavity is nontransparent, due to the re-circulation of water back into the cavity. Highlights: Ventilated cavitating flow structure is studied by experimental and numerical methods. The method with filter-based model is proposed to simulate the ventilated cavity. The influence of Q v and Fr on the gas leakage behavior is discussed. The mechanism of two types of re-entrant behaviors is illustrated.